Shapes of macromolecules in good solvents: field theoretical renormalization group approach - Blavatska, V.; von Ferber, C.; Holovatch, Yu. (Condensed Matter Physics, 2011)
In this paper, we show how the method of field theoretical reno rmalization group may be used to analyze universal shape properties of long polymer chains in porous environment. So far such analytical calculations were primarily focussed on the scaling exponents that govern conformational properties of polymer macromolecules. However, there are other observables that along with the scaling exponents are universal (i.e. independent of the chemical structure of macromolecules and of the solvent) and may be analyzed within the renormalization group approach. Here, we address the question of shape which is acquired by the long flexible polymer macromolecule when it is immersed in a solve nt in the presence of a porous environment. This question is of relevance for understanding of the behavior of macromolecules in colloidal solutions, near microporous membranes, and in cellular environment. To this end, we consider a previously suggested model of polymers in d-dimensions [V. Blavats’ka, C. von Ferber, Yu. Holovatch, Phys. Rev. E, 2001, 64, 041102] in an environment with structural obstacles, characterized by a pair correlation function h(r), that decays with distance r according to a power law: h(r) ∼ r−a. We apply the field-theoretical renormalization group ap-proach and estimate the size ratio hR²ei/hR²Gi and the asphericity ratio Aˆd up to the first order of a double ε = 4−d, δ = 4−a expansion. У статтi ми показуємо, яким чином можна застосувати метод теоретико-польової ренормалiзацiйної групи для аналiзу унiверсальних властивостей форм довгих гнучких полiмерних ланцюгiв у пористому середовищi. До цього часу такi аналiтичнi розрахунки в основному торкались показникiв скей-лiнгу, що визначають конформацiйнi властивостi полiмерних макромолекул. Проте, iснують й iншi спостережуванi величини, що, як i показники скейлiнгу, є унiверсальними (тобто незалежними вiд хiмiчної структури як макромолекул, так i розчинника), а отже можуть бути проаналiзованi в межах пiдходу ренормалiзацiйної групи. Ми цiкавимось питанням, якої форми набуває довга гнучка полiмерна макромолекула у розчинi в присутностi пористого середовища. Це питання є суттєвим для розумiння поведiнки макромолекул у колоїдних розчинах, поблизу мiкропористих мембран, а також у клiтинному середовищi. Ми розглядаємо запропоновану ранiше модель полiмера у d-вимiрному просторi [V. Blavats’ka, C. von Ferber, Yu. Holovatch, Phys. Rev. E, 2001, 64, 041102] у середовищi iз структурними неоднорiдностями, що характеризуються парною кореляцiйною функцiєю h(r), яка спадає iз вiдстанню r згiдно степеневого закону: h(r) ∼ r−a. Застосовуємо пiдхiд теоретико-польової ре-нормалiзацiйної групи i оцiнюємо вiдношення розмiрiв hR²ei/hR²Gi та асферичнiсть Aˆd до першого порядку ε = 4−d, δ = 4−a-розкладу.